2015
DOI: 10.1002/2014ms000361
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative attribution of major driving forces on soil organic carbon dynamics

Abstract: Soil organic carbon (SOC) storage plays a major role in the global carbon cycle and is affected by many factors including land use/management changes (e.g., biofuel production-oriented changes). However, the contributions of various factors to SOC changes are not well understood and quantified. This study was designed to investigate the impacts of changing farming practices, initial SOC levels, and biological enhancement of grain production on SOC dynamics and to attribute the relative contributions of major d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…4 ). This finding agreed with previous studies that showed soil with high SOC levels may tend to release carbon 10 37 because SOC tends to progress toward its equilibrium level which depends on the land use and management practices applied for a given site with a given climate condition 38 39 . Land-use change could alter the equilibrium level, and thus extensive stover harvesting in high SOC areas (vulnerable areas) would likely result in substantial release of carbon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4 ). This finding agreed with previous studies that showed soil with high SOC levels may tend to release carbon 10 37 because SOC tends to progress toward its equilibrium level which depends on the land use and management practices applied for a given site with a given climate condition 38 39 . Land-use change could alter the equilibrium level, and thus extensive stover harvesting in high SOC areas (vulnerable areas) would likely result in substantial release of carbon.…”
Section: Discussionsupporting
confidence: 92%
“…For proper projection of plant growth and grain production, the EDCM model also took into account the enriched CO 2 effects 66 and the biological enhancement of grain production owing to gene technology, which can be found in our previous national-scale assessment 2 38 . Specifically, the corn yield has experienced continuous increase in the past century and will also increase but with a much lower rate for the coming decades 2 38 . The auto-fertilization function of the model based on N stress was implemented to ensure nitrogen content would not be a limiting factor of crop growth in this study.…”
Section: Methodsmentioning
confidence: 99%
“…No-till without mulch cover drastically reduces crop yields in semiarid regions (Rusinamhodzi et al 2011), strongly reduces the C sink potential (Wu et al 2015), and decreases the SOC pool (Blanco-Canqui 2013).…”
Section: System Approachmentioning
confidence: 99%
“…Accounting for about 62% of global soil carbon, soil organic carbon (SOC) is an important component that affects physical, chemical, and biological processes in soils [ Lal , ; Fang et al ., ; Wu et al ., ], and a key variable for global and regional numerical weather prediction models (NWPMs) and earth system models (ESMs) [ Batjes , ; Li et al ., ; Todd‐Brown et al ., ; DeBrogniez et al ., ]. As NWPMs and ESMs have become more sophisticated, there has been growing demand for more detailed information of SOC levels and spatial variations across geographic areas [ Sanchez et al ., ; Shangguan et al ., ], which can contribute to more accurate estimations of SOC stock [ Meersmans et al ., ; Yang et al ., ] and to improve simulations of climate and earth system models [ Shi et al ., ; De Lannoy et al ., ].…”
Section: Introductionmentioning
confidence: 99%